Stent-assisted coiling of intracranial aneurysms aided by virtual parent artery reconstruction - Karmonik, Christof (2005)
Summary: The availability of stents designed specifically for use in the intracranial vasculature has increased the use of stent-assisted coiling for treatment of wide-necked and complex intracranial aneurysms. We present a technique for pretreatment planning and visualization of a virtual stent within the parent artery by using a virtual reconstruction of the parent artery across the aneurysm neck. As illustrated by 2 clinical examples, this method provides information not otherwise available regarding the location of portions of the stent that are not visible on fluoroscopy. During treatment, this information enhances the ability to determine the location of coils in relation to the stent boundaries and should thereby improve the ability to avoid parent artery compromise.